Bedside Prediction of Neonatal Pulmonary Maturity by Single Step Gastric Aspirate Shake Test - Khairul Alam, Mohammad; Sultana, Nadira; Zahirul Islam, Mohammad; Ahmed, Faruk; Hashem, Md Abul (Medicine Today, 2025)
Introduction: Respiratory distress syndrome occurs primarily in preterm neonates. Such a baby may need advanced support like NICU admission for ventilation. Preterm LBW is a common problem in our country. Available few centers cannot accommodate all preterm LBW babies. So early prediction of RDS by a simple tool may help to decide whether a baby needs NICU admission for ventilation or not and early referral from a low-facility hospital would be possible. Aims: To assess the reliability of gastric aspirate shake test in predicting respiratory distress syndrome in newborns immediately after birth. Materials and Methods: This prospective study was conducted in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh, from September 2009 to May 2010. We included 60 inborn neonates who were admitted to BSMMU and DMCH. Of all the newborns, 30 were pre-term and 30 were term. Results: In this study, we found that 75% of preterm neonates with a negative shake test (9 out of 12) developed RDS, and 50% of preterm neonates with an intermediate result (2 out of 4) developed RDS. None of the 14 preterm neonates with a positive shake test developed RDS. None of the term neonates developed RDS. Conclusion: It can be concluded that the gastric aspirate shake test is a simple, inexpensive, non-invasive, and reliable test. It can be an excellent beside tool for predicting respiratory distress syndrome in newborns immediately after birth. Medicine Today 2025, Vol.37 (1): 64-68